The Philippine Independent and Episcopal Churches : a study of their histories and the factors that led them to a concordat relationship - Canlas, Querubin D. ([n.p.] : South East Asia Graduate School of Theology, 1980)
This work is a story--a tale-- of two churches which are the Philippine Independent Chucrh (or Iglesia Filipina Independiente) and the philippine Episcopal Church, (basically the Protestant Episcopal Church in the United States of America, or simply the Episcopal Church, U.S.A.). It is a narrative of their histories in the light of the working Concordat relationship which subsequently brought them together. The individual tale of each discloses a different background or beginning, set under different circumstances. But more significant than anything else in their growing together following the Concordat.
In partial fulfillment of the Degree of Doctor of Theology in Church History
A Thesis submitted to the South East Asia Graduate School of Theology
Thesis (D.TH.) - South East Asia Graduate School of Theology
Keywords: Iglesia Filipina Independiente -- History; Philippine Episcopal Church -- History